2019
DOI: 10.18203/2320-1770.ijrcog20193582
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of maternal deaths and maternal near misses due to major obstetric haemorrhage at a tertiary care centre in India

Abstract: Background: Maternal near miss (MNM) is now widely accepted as a better indicator of maternal health than maternal death and reflects the quality of obstetric care in a particular institution. Methods: This is a retrospective study conducted at Lady Hardinge Medical College and Smt. Sucheta Kriplani Hospital over a period of 12 months (April 2016-March 2017), of all cases of maternal death and near miss maternal deaths due to major obstetric haemorrhage(MOH). Results: During the period reviewed, there were 13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The second most common indirect cause of deaths in present study was haemorrhage 20% which was similar to study by Agarwal et al 14 Several publications have documented an increase in the incidence of obstetric haemorrhage particularly PPH over the recent years. It is important to identify the causative factors for obstetrical haemorrhage so that remedial measures can be taken to reduce their occurrence or severity.…”
Section: Discussionsupporting
confidence: 90%
“…The second most common indirect cause of deaths in present study was haemorrhage 20% which was similar to study by Agarwal et al 14 Several publications have documented an increase in the incidence of obstetric haemorrhage particularly PPH over the recent years. It is important to identify the causative factors for obstetrical haemorrhage so that remedial measures can be taken to reduce their occurrence or severity.…”
Section: Discussionsupporting
confidence: 90%
“…Among other studies, Agrawal et al reported that the mode of delivery was vaginal in 21% of cases and caesarean in 79% of cases. 16 Most of the women were delivered by caesarean section (58.56%) in the study by Renuka et al 17 Similarly in study by Chowdhury et al 63.92% had caesarean section. 15 In Thurn et al 5.7% cases had caesarean deliveries.…”
Section: Mode Of Deliverymentioning
confidence: 92%
“…Among other studies, Agarwal et al reported that the number of maternal deaths occurring amongst all women with massive obstetric haemorrhage was 3.33%. 16 No mortality was reported by Chawla et al, Vaid et al and Renuka et al 17,18,25…”
Section: Adverse Blood Transfusion Reactionsmentioning
confidence: 93%
See 2 more Smart Citations